The H2S-Releasing Naproxen Derivative ATB-346 and the Slow-Release H2S Donor GYY4137 Reduce Intestinal Inflammation and Restore Transit in Postoperative Ileus - Van Dingenen, Jonas; Pieters, Leen; Vral, Anne; Lefebvre, Romain A. (Frontiers in Pharmacology, 2019)
Objective: Intestinal inflammation triggers postoperative ileus (POI), commonly seen after abdominal surgery and characterized by impaired gastrointestinal transit; when prolonged, this leads to increased morbidity. Hydrogen sulfide (H2S) is recognized as an important mediator of many (patho)physiological processes, including inflammation, and is now investigated for anti-inflammatory application. Therefore the aim of this study was to investigate the effect of the H2S-releasing naproxen derivative ATB-346, developed to reduce gastrointestinal injury by naproxen, and the slow-release H2S donor GYY4137 on intestinal inflammation and delayed gastrointestinal transit in murine POI. Methods: C57Bl6J mice were fasted for 6 h, anesthetized and after laparotomy, POI was induced by compressing the small intestine with two cotton applicators for 5 min (intestinal manipulation; IM). GYY4137 (50 mg/kg, intraperitoneally), ATB-346 (16 mg/kg, intragastrically) or naproxen (10 mg/kg, intragastrically) were administered 1 h before IM. At 24 h postoperatively, gastrointestinal transit was assessed via fluorescent imaging, and mucosa-free muscularis segments were prepared for later analysis. Inflammatory parameters and activity of inducible nitric oxide synthase (iNOS) and cyclo-oxygenase (COX)-2 were measured. Histological examination of whole tissue sections was done on hematoxylin-eosin stained slides. Results: Pre-treatment with GYY4137 (geometric centre; GC: 7.6 ± 0.5) and ATB-346 (GC: 8.4 ± 0.3) prevented the delayed transit induced by IM (GC: 3.6 ± 0.5 versus 9.0 ± 0.4 in non-operated controls) while naproxen only partially did (GC: 5.9 ± 0.5; n = 8 for all groups). GYY4137 and ATB-346 significantly reduced the IM-induced increase in muscular myeloperoxidase (MPO) activity and protein levels of interleukin (IL)-6, IL-1β and monocyte chemotactic protein 1; the reduction by naproxen was less pronounced and only reached significance for MPO activity and IL-6 levels. All treatments significantly reduced the increase in COX-2 activity caused by IM, whereas only GYY4137 significantly reduced the increase in iNOS activity. Naproxen treatment caused significant histological damage of intestinal villi. Conclusion: The study shows that naproxen partially prevents POI, probably through its inhibitory effect on COX-2 activity. Both ATB-346 and GYY4137 were more effective, the result with GYY4137 showing that H2S per se can prevent POI.